Art beyond itself : anthropology for a society without a story line - García Canclini, Néstor (Duke University Press, 2014)
First published in Spanish in 2010, Art beyond Itself is Néstor García Canclini's deft assessment of contemporary art. The renowned cultural critic is attentive to particular artworks; to artists including Francis Alÿs, León Ferrari, Teresa Margolles, Antoni Muntadas, and Gabriel Orozco; and to efforts to preserve, for art and artists, some degree of independence from religion, politics, the media, and the market.